[P4H]+[Al(OTeF5)4]−: protonation of white phosphorus with the Brønsted superacid H[Al(OTeF5)4](solv)12. Issue 36 (23rd August 2018) - Wiesner, Anja; Steinhauer, Simon; Beckers, Helmut; Müller, Christian; Riedel, Sebastian
Abstract : The structure of protonated white phosphorus in solution has been revealed for the first time. Abstract : A sustainable transformation of white phosphorus (P4 ) into chemicals of higher value is one of the key aspects in modern phosphorus research. Even though the chemistry of P4 has been investigated for many decades, its chemical reactivity towards the simplest electrophile, the proton, is still virtually unknown. Based on quantum-chemical predictions, we report for the first time the successful protonation of P4 by the Brønsted acid H[Al(OTeF5 )4 ](solv) . Our spectroscopic results are in agreement with acid-mediated activation of P4 under protonation of an edge of the P4 -tetrahedron and formation of a three-center two-electron P–H–P bond. These investigations are of fundamental interest as they permit the activation of P4 with the simplest electrophile as a new prototype reaction for this molecule.